2011
DOI: 10.1007/s11274-011-0697-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the molar fraction of 4-hydroxybutyrate in Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) by biological fermentation and enzymatic degradation

Abstract: The regulation of 4-hydroxybutyrate (4HB) molar fraction in the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] of a local isolate Cupriavidus sp. USMAA1020 was attempted by employing a feeding strategy through fed-batch fermentation in 100-L fermenter. The growth of Cupriavidus sp. USMAA1020 was enhanced by frequently feeding carbon and nitrogen at a ratio of 5 (C/N 5) using a DO-stat with cascade mode at 20% (v/v) dissolved oxygen (DO). The feeding of C/N 5 and the use of the DOstat mode were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Sequential feeding strategy is also known to result in improved production of copolymer and higher accumulation of secondary monomer 24. By employing this modified two‐stage cultivation for P(3HB‐ co ‐4HB) biosynthesis, the regular time consuming process of enrichment followed by aseptic transfer of bacterial cells into nitrogen‐free MM containing carbon source could be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential feeding strategy is also known to result in improved production of copolymer and higher accumulation of secondary monomer 24. By employing this modified two‐stage cultivation for P(3HB‐ co ‐4HB) biosynthesis, the regular time consuming process of enrichment followed by aseptic transfer of bacterial cells into nitrogen‐free MM containing carbon source could be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications of surfaces Mechanical modifications (1) Creating physical micro-rough, grooves or pores by enzyme degradation [63], alkali hydrolysis [64], particulate leaching or freeze-drying methods [65].…”
Section: Types Of Modificationsmentioning
confidence: 99%
“…This strategy has been reported in some studies for the production of different PHA polymers. Faezah et al [11] reported the use of the DO-stat mode to feed oleic acid and/or γ-butyrolactone to Cupriavidus sp. USMAA1020, as a strategy to regulate the molar fraction of 4-hydroxybutyrate in the P(3HB-co-4HB) polymer.…”
Section: International Journal Of Polymer Sciencementioning
confidence: 99%
“…However, the process set-up requires the selection of a suitable substrate feeding strategy to properly control the concentration of the carbon source throughout the fed-batch phase. Several strategies are available to feed the cultures and have been tested for PHA production from different substrates, including, among others, pulse feeding [4,5], continuous feeding with defined feed rate [6,7], exponential feeding [8,9], control of nutrient feed through dissolved oxygen (DO) concentration (DO-stat mode) [10][11][12], and pH control (pH-stat mode) [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation